Necessity as a Function of Skewness - Sorjonen, Kimmo; Wikström Alex, Jenny; Melin, Bo (Frontiers in Psychology, 2017)
With Necessary Condition Analysis (NCA), a necessity effect is estimated by calculating the amount of empty space in the upper left corner in a plot with a predictor X and an outcome Y. In the present simulation study, calculated necessity effects were found to have a negative association with the skewness of the predictor and a positive association with the skewness of the outcome. Also the standard error of the necessity effect was found to be influenced by the skewness of the predictor and the skewness of the outcome, as well as by sample size, and a way to calculate a confidence interval for the necessity effect is presented. At least some of the findings obtained with NCA are well within the range of what can be expected from the skewness of the predictor and the outcome alone.